HUBUNGAN KEGIATAN EKSTRAKURIKULER DENGAN PEMBENTUKAN KARAKTER SISWA KELAS TINGGI SDN 13 BIRU KABUPATEN BONE - Hasanah, Uswatun; Muliadi; Jauhar, Sitti (MACCA : Science-Edu Journal, 2025)
This study aims to analyze the relationship between extracurricular activities and character formation of high-class students at SDN 13 Biru, Tanete Riattang District, Bone Regency. The research was conducted in the period from November 15 to December 13, 2024, using a quantitative approach. Data was collected through filling out questionnaires by 66 students and analyzed with descriptive and inferential statistics using IBM SPSS Statistic Version 26. The results showed that most students (59.1%) had a moderate level of involvement in extracurricular activities, with an average score of 60.21. The formation of students' character also showed similar results, with an average score of 60.65. Analysis of the hypothesis test using the Spearman's rho test revealed that there was a moderate positive relationship between extracurricular activities and the formation of students' character (r = 0.472, p < 0.05), so it can be concluded that ekstracurricular activities have a significant relationship in the character building of high-class students of SDN 13 Biru, Tanete Riattang District, Bone Regency.